Characteristics of the household sector of the hidden economy in an emerging economy - Sandra Sookram; Friedrich G. Schneider; Patrick Kent Watson (Johannes Kepler University of Linz, Department of Economics, 2006)
Using the case study of Trinidad and Tobago we investigate for an emerging economy the socioeconomic, demographic, and attitudinal characteristics that influence the propensity of individuals in the household sector to participate in the hidden economy and their perception of the risk of detection by tax authorities in doing so. To this end we analyze data gathered from a unique cross-sectional field survey covering 570 households. Our econometric results using multinomial logit and ordered probit models suggest that individual household members are motivated to undertake hidden economic activity because they believe taxes are too high, their incomes are too low, they have dependents to support, and they believe that the resulting tax evasion will go undetected.
Keywords: C25; C51; E26; 330; hidden economy; multinomial logit and ordered probit models; emerging economies; Schattenwirtschaft; Privater Haushalt; Aufstrebende Märkte; Modellierung; Logit-Modell; Probit-Modell; Schätzung; Trinidad und Tobago